Organized Tawarruq in Bursa Souq al-Sila’, Malaysia: a critical examination of Shariah compliance - Eldodo Saeed, Abdelrahman Musa; Hamdan, Hamdino; Abdul Razak, Dzuljastri; Khaliq, Ahmad (Zek Rokman Resources, 2025)
Bursa Souq al-Sila’ (BSAS) is Malaysia’s first Shariah-compliant commodity trading platform, using crude palm oil to facilitate Islamic finance contracts such as Murabaha and organized Tawarruq. While organized Tawarruq has become a key liquidity-management tool for Islamic banks, its resemblance to interest-based lending (riba) has sparked intense debate among Shariah scholars. This study, therefore, aims to (1) map the operational mechanism of organized Tawarruq on BSAS, (2) evaluate its Shariah compliance, (3) assess its effectiveness in meeting short-term liquidity needs, and (4) propose actionable recommendations for strengthening Shariah governance and regulatory oversight in Malaysia. Adopting a qualitative approach, we draw on secondary sources and semi-structured interviews with Islamic finance experts at the International Islamic University Malaysia (IIUM). Our findings reveal that organized Tawarruq is widely and rapidly adopted yet remains controversial: some jurists condemn it as a legal stratagem masking riba, while others regard it as a necessary innovation in the absence of viable alternatives. Operational issues—such as commodity availability, delivery timelines, and customer awareness further affect its real-world application. We conclude by calling for clearer contract terms, enhanced e-certificate controls on BSAS, and targeted education initiatives for practitioners and customers. These measures will help reconcile liquidity-management imperatives with rigorous Shariah compliance, advancing both the ethical integrity and practical effectiveness of Islamic financial instruments.